Avoiding the New Mediocre : Raising Long-Term Growth in the Middle East and Central Asia - Mitra, Pritha (Departmental Papers; Departmental Paper ;, 2016)
Raising the Middle East and Central Asia's long-term growth prospects is critical for meeting the region's pressing need for jobs and higher living standards.